Dental Academic Degrees in Germany Compared to the USA - Nikoletta Vargas; Georgios E. Romanos (MDPI AG, 2022)
There are different avenues for obtaining postgraduate doctoral/Ph.D. degrees in Germany and abroad. Depending on their interests and career plans, candidates can choose a postgraduate doctorate/Ph.D. that focuses on a career in academia or a doctorate that does not involve all elements of a Ph.D. and is obtained for the title's sake. Germany offers this type of diversity and flexibility, whereas the USA postgraduate doctorate model presents a more structured doctorate. The current article provides insight regarding various and more flexible pathways for obtaining a postgraduate doctorate by comparing the German and the American model. The diversity of academic degrees in dentistry and medicine, such as postgraduate doctoral degrees and the higher postdoctoral degrees available in Germany for graduates interested in academia, makes educational evaluation processes and credentials recognition challenging. The lack of transparency and a systematic approach for the academic acknowledgment of the different scientific values of each doctorate type is creating confusion, primarily when German postgraduate doctorate holders pursue academic careers internationally. The current article aims to enhance the knowledge about the different academic degrees and facilitate the educational evaluations, specialty applications, and employment processes. Understanding the additional scientific value of each doctorate type offered in Germany is imperative for their credential recognition internationally.